(untitled) (Práxis Educativa, 2022)
This study aimed to: identify digital platforms and technologies (DPT) most used in school activities; check effects of the pandemic due to COVID-19, on this use; systematize the advantages or contributions and problems/difficulties perceived. Questionnaires answered by 1,753 teachers and 2,041 students from Portuguese public schools revealed an increase in the frequency of use of DPT, for purposes identical to the pre-pandemic ones. Both groups considered that DPT promote innovative educational practices, being the internet access and the lack of knowledge in this area obstacles. During the quarantine, teachers referred mainly to the lack of communication with students and the subsequent social inequality, and students referred to the difficulty in understanding the subjects and the lack of contact with colleagues and teachers. In conclusion, it is necessary to invest in generalized access to the internet an DPTs and in the development of digital skills of teachers and students, in order to reduce social inequalities. Keywords: Digital technologies. Basic Education. Digital education.